A Symbiotic View of Life: We Have Never Been Individuals - Gilbert, Scott F.; Sapp, Jan; Tauber, Alfred I. (The Quarterly Review of Biology, 2012)
The notion of the “biological individual” is crucial to studies of gen etics, immunology, evolution, development, anatomy, and physiology. Ea ch of these biological subdisciplines has a specific conception of ind ividuality, which has historically provided conceptual contexts for in tegrating newly acquired data. During the past decade, nucleic acid an alysis, especially genomic sequencing and high-throughput RNA techniqu es, has challenged each of these disciplinary definitions by finding s ignificant interactions of animals and plants with symbiotic microorga nisms that disrupt the boundaries that heretofore had characterized th e biological individual. Animals cannot be considered individuals by a natomical or physiological criteria because a diversity of symbionts a re both present and functional in completing metabolic pathways and se rving other physiological functions. Similarly, these new studies have shown that animal development is incomplete without symbionts. Symbio nts also constitute a second mode of genetic inheritance, providing se lectable genetic variation for natural selection. The immune system al so develops, in part, in dialogue with symbionts and thereby functions as a mechanism for integrating microbes into the animal-cell communit y. Recognizing the “holobiont”—the multicellular eukaryote plus its co lonies of persistent symbionts—as a critically important unit of anato my, development, physiology, immunology, and evolution opens up new in vestigative avenues and conceptually challenges the ways in which the biological subdisciplines have heretofore characterized living entitie s.
Keywords: evolution; holobiont; individuality; symbionts; symbiosis